GAO cost estimating and assessment guide : best practices for developing and managing capital program costs. - Richey, Karen; Echard, Jennifer; Cha, Carol (United States Govt. Accountability Office, 2009)
The U.S. Government Accountability Office is responsible for, among other things, assisting the Congress in its oversight of the federal government, including agencies' stewardship of public funds. To use public funds effectively, the government must meet the demands of today's changing world by employing effective management practices and processes, including the measurement of government program performance. In addition, legislators, government officials, and the public want to know whether government programs are achieving their goals and what their costs are. To make those evaluations, reliable cost information is required and federal standards have been issued for the cost accounting that is needed to prepare that information. We developed the Cost Guide in order to establish a consistent methodology that is based on best practices and that can be used across the federal government for developing, managing, and evaluating capital program cost estimates.